Instigating prevalent abiotic stress resilience in crop by exogenous application of phytohormones and nutrient - Swain, Rinny; Sahoo, Smrutishree; Behera, Mamata; Rout, Gyana Ranjan (Frontiers in Plant Science, 2023)
In recent times, the demand for food and feed for the ever-increasing population has achieved unparalleled importance, which cannot afford crop yield loss. The important approaches to identify the new genotypes to cope with higher yield potential targeting several abiotic stresses and to modify the target metabolic pathway by use of different phytohormones. The phytohormones like the classical auxins, cytokinins, ethylene, and gibberellins, as well as more recent members including brassinosteroids, jasmonic acids, etc., were very crucial for developing abiotic stress-tolerant crop plants maintaining growth and survival under stress conditions. Along with phytohormones, both macro and micronutrients have gained more significant attention because of their vast capacity to boost crop plants' tolerance for abiotic stresses. Major benefits such as reduction of ionic toxicity, water balance preservation, gaseous exchange modification, and oxidative stress. Recent reports revealed that there is a strong relationship between hormonal stimulation and nutritional homeostasis in plants under stress situations by demonstrating a cross-talk between phytohormones and nutrients. This present review highlighted the alteration of metabolic activities caused by abiotic stress in various crops, the changes of vital functions through the application of exogenous phytohormones and nutrition, as well as their interaction.